2015
DOI: 10.1111/saje.12079
|View full text |Cite
|
Sign up to set email alerts
|

Public Debt and Economic Growth in Emerging Market Economies

Abstract: This paper studies the relationship between public debt and economic growth for selected emerging markets performing panel data estimations. Several regressor variables are included, but the main focus is on public debt. The results reveal a significant positive correlation between public debt and the subsequent growth rate of per capita GDP. Population and investment also yield a significant positive influence on subsequent growth, whereas the initial real GDP per capita gives a negative influence. Other vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…This relation may be different as regards developing and emerging market economies, as has been found for instance by Fincke and Greiner (2014), as they are on the transition path. Further studies merge different types of countries and perform dynamic panel threshold estimations, such an estimation may also be of interest for our set of economies for future studies in order to elaborate further on the non-linearities of the relationship.…”
Section: (4) 137-150 2015mentioning
confidence: 96%
See 1 more Smart Citation
“…This relation may be different as regards developing and emerging market economies, as has been found for instance by Fincke and Greiner (2014), as they are on the transition path. Further studies merge different types of countries and perform dynamic panel threshold estimations, such an estimation may also be of interest for our set of economies for future studies in order to elaborate further on the non-linearities of the relationship.…”
Section: (4) 137-150 2015mentioning
confidence: 96%
“…But, for emerging market economies the relation may be different. For example, in Fincke and Greiner (2014) a positive correlation between public debt and economic growth has been detected, suggesting that the relation between debt and growth in emerging market economies may be different from that in industrialized countries. One explanation for that difference could be that this relation is different in fast growing economies on the transition path from that in industrialized countries that can be characterized by a steady state growth path.…”
Section: Discussionmentioning
confidence: 99%
“…While applying the ARDL technique to examine the external debt and economic growth nexus in Nigeria from 1984-2018, Ohiomu (2020) concluded that debt overhang and crowding out variables aversely effect growth. On their part, Fincke and Greiner (2015) examine the debt-growth nexus for 8 emerging economies and concluded on a positive effect of debt on growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also find that the quality of domestic debt (whether it is in marketable securities, positive real interest rates and debt issued to the non-bank sector) matters a great deal towards its impact on growth. Other notable studies reporting positive effects are Egert (2015) and Fincke and Greiner (2015).…”
Section: The Debt and Growth Literaturementioning
confidence: 99%